(untitled) (Baghdad Science Journal, 2025)
The present work includes the preparation and characterization ofCo(II) , Ni(II), Pd(II), Fe(III) , Ru(III),Rh(III), Os(III) , Ir(III) , Pt(IV) and VO(IV)complexes of a new ligand 4-[(1-phenyl-2,3-dimethyl-3-pyrozoline-5-one)azo]-N,N-dimethylanline (PAD). The product (PAD) was isolated,studies and characterized by phsical measurements,i.e., (FT-IR), (UV) Spectroscopy and elemental analysis(C.H.N). The prepared complexes were identified and their structural geometric were suggested in solid state by using flame atomic absorption, elemental analysis(C.H.N), (FT-IR) and (UV-Vis) Spectroscopy, as well as magnetic susceptibility and conductivity measurements . The study of the nature of the complexes formed in( ethanolic solution) following the mole ratio method,gave results which were compared successfully with those obtained from solid state studies. The apparent stability constant of the complexes have been studied with the time and their color were stable for more than ( 6 ) hours , as well as the molar absorptivities have been calculated.The antibacterial activity for the ligand (PAD) and their metal complexes were studied against two selected micro - organisms [(Klesbiella pneumonia) as gram negative] and[( Streptococcus faecalis) as gram positive]. Further more the antifungl activity against two micro-organism (Candida albicans and Aspergillus flavus) were studied for the ligand (PAD) and their metal complexes .